Importance of motif and onamentation in mosque architecture - Othman .R (Penerbit UKM, 2011)
Mosque, as a symbol of Islamic architecture plays an important role in reflecting the superiority of Allah the Almighty. One of the successful ways is through aesthetical quality. Aesthetic value in the history of Islamic art and architecture is normally portrayed by its motifs and ornamentation that normally applied to the wall surfaces of Islamic buildings. Contemporary mosques, on the other hand, portray its aesthetical quality through the majestic look, emphasized by the existence of domes and minarets. Research on mosque architecture contributed to variety of knowledge. This paper focuses on the application of Islamic art to mosque interior that contributes to the high level of aesthetical value. High degree of aesthetical quality includes the employment of appropriate motifs and ornamentation on mosque interior, thus suggesting that the application of motif and ornamentation to be part of the mosque components and not as mere decorations. The aim is for existing and future Malaysian mosques to have meaningful as well as beautiful interior.